Does malnutrition influence hospital reimbursement? A call for malnutrition diagnosis and coding - Fernandes, AC (2020)
Objectives: The aim of this study was to determine how diagnosing and coding of malnutrition in an internal medicine ward setting influences potential hospital reimbursement. Methods: Patients admitted to the internal medicine ward of Centro Hospitalar do Médio Ave between April 24 and May 22, 2018 were screened by Nutritional Risk Screening 2002, and patients classified as at "risk for malnutrition" were assessed by the Patient-Generated Subjective Global Assessment (PG-SGA). For each patient, medical coders simulated coding, taking into account the malnutrition diagnosis by PG-SGA, and compared it with the real coding as retrieved from the medical records. For the coding, the Diagnosis-Related Group and Severity of Illness were determined, allowing the calculation of hospitalization cost (HC) according to Portuguese Ministerial Directive number 207/2017. The increase of HC in this subsample was extrapolated to the number of patients admitted during 2018, to obtain the estimated unreported annual HC. Results: Of the 71% (92/129) participants having malnutrition risk according to Nutritional Risk Screening 2002, 86% were malnourished. Including malnutrition diagnosis in the coding of malnourished patients increased the level of Severity of Illness in 39% of cases and increased HC for this subsample, resulting in €52 000. Extrapolating for the annual HC, total HC reached €1.3 million. Conclusions: Identifying malnourished patients and including this highly prevalent diagnosis in medical records allows malnutrition coding and consequent increase of HC. This can improve the potential hospital reimbursement, which could contribute to the quality of patient care and economic sustainability of hospitals.